Human Resource Practices and Employee Engagement in the Banking Sector in Uganda - Kembabazi, Stella N (2013)
The ever challenging world of business has made it more important than ever for organizations to learn how to keep up and over take their competition. Organizations have to learn to adapt to the uncertain financial climate brought on by the global economic crisis. The use of HR strategies is one of the most effective ways to main competitiveness as employees are regarded as the foundation of the organizations. Managers must therefore learn how to strengthen this foundation my ensuring they are emotionally and intellectually engaged their jobs and this might require the use of such motivating tools such as rewards and recognition as well are career advancement and job security. By surveying employees in the banking sector in Uganda, this research will try to understand, what factors contribute to employee engagement and the data will be analyzed using SPSS 20 to test for reliability and validity.